Answer:
x=(-2/3)
Step-by-step explanation:
(9x+13)^2=49
√(9x+13)^2=√49
9x+13=7
9x+13-13=7-13
9x=-6
9x÷9=-6/9
x=-6/9
-6/9=-2/3
3f+3=t
s=2f
21=f+s+t
21=f+(2f)+(3f+3)
21=6f+3
18=6f
3=first
6=second
12=third
The correct answer is number one, number four, and number five. Please park Brainliest if helpful. Thanks
Answer:
39V3 Sq.units of that will help you
Your answer is A.
why:
because if the y value changes then your vertical will change. if your x changes than your horizontal will change. if it’s compressed, your x value is less than 1.